Characteristics and outcomes of adolescents living with perinatally acquired HIV within Southern Africa. (1st December 2020) - Tsondai, Priscilla R.; Braithwaite, Kate; Fatti, Geoffrey; Bolton Moore, Carolyn; Chimbetete, Cleophas; Rabie, Helena; Phiri, Sam; Sawry, Shobna; Eley, Brian; Hobbins, Michael A.; Boulle, Andrew; Taghavi, Katayoun; et al.
Abstract : Background: Using data from 15 International epidemiology Databases to Evaluate AIDS in Southern Africa sites, we compared the characteristics and outcomes of adolescents living with perinatally acquired HIV (ALPH). Methods: We included ALPH entering care aged less than 13 years with at least one HIV care visit during adolescence (10–19 years). We compared the characteristics and cross-sectional outcomes: transfer out, loss to follow-up (no visit in the 12 months prior to database closure), mortality, and retention between those who entered care aged less than 10 vs. aged 10–13 years; and explored predictors of mortality after age 13 years using Cox Proportional Hazards models. Results: Overall, 16 229 (50% female) ALPH who entered HIV care aged less than 10 years and 8897 (54% female) aged 10–13 years were included and followed for 152 574 person-years. During follow-up, 94.1% initiated antiretroviral therapy, with those who entered care aged less than 10 more likely to have initiated antiretroviral therapy [97.9%, 95% confidence interval (CI) 97.6; 98.1%] than those who presented aged 10–13 years (87.3%, 95% CI 86.6; 88.0%). At the end of follow-up, 3% had died (entered care aged <10 vs. 10–13 years; 1.4 vs. 5.1%), 22% were loss to follow-up (16.2 vs. 33.4%), and 59% (66.4 vs. 45.4%) were retained. There was no difference in the risk of dying after the age of 13 years between adolescents entering care aged less than 10 vs. 10–13 years (adjusted hazard ratio 0.72; 95% CI 0.36; 1.42). Conclusion: Retention outcomes for ALPH progressively worsened with increasing age, with these outcomes substantially worse among adolescents entering HIV care aged 10–13 vs. less than 10 years. Abstract : Supplemental Digital Content is available in the text